2015
DOI: 10.1097/md.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Transcatheter Arterial Embolization for Acute Renal Hemorrhage

Abstract: The aims of this study were to identify arteriographic manifestations of acute renal hemorrhage and to evaluate the efficacy of emergency embolization. Emergency renal artery angiography was performed on 83 patients with acute renal hemorrhage. As soon as bleeding arteries were identified, emergency embolization was performed using gelatin sponge, polyvinyl alcohol particles, and coils. The arteriographic presentation and the effect of the treatment for acute renal hemorrhage were analyzed retrospectively. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The patients are recommended to be routinely sent to the observation room for careful surveillance at early postoperative period. RH should be alerted if the patient presents with progressively decrease of hemoglobin, hypotension, tachycardia and acute ipsilateral abdominal/flank pain [ 6 , 14 , 15 ]. Rapid diagnosis of RH relies on proper imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The patients are recommended to be routinely sent to the observation room for careful surveillance at early postoperative period. RH should be alerted if the patient presents with progressively decrease of hemoglobin, hypotension, tachycardia and acute ipsilateral abdominal/flank pain [ 6 , 14 , 15 ]. Rapid diagnosis of RH relies on proper imaging.…”
Section: Discussionmentioning
confidence: 99%
“…1 Gradually, with advances in studies, trans-catheter arterial embolization (TAE) has been widely accepted, with the advantages of minimal invasiveness and a high success rate, as one of the most effective treatment options for acute RH. [3][4][5] In clinical settings, acute RH patients sometimes present with a coagulopathic condition, and a worse outcome has been proven in these patients than in those without coagulopathy. 6 MacLeod et al 7 commented that coagulopathy is an independent predictor of mortality even in the presence of other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of minor and major complications grouped together is 10%; considering major hemorrhages only, those requiring blood transfusions occur in up to 4% of the cases while those requiring arterial embolization occur in up to 1% (Pabon-Ramos et al 2016). Nephrectomy is reserved only for the cases in which the minimally invasive endovascular treatment fails (Summerton et al 2012); actually the technical success of transarterial embolization of iatrogenic renal hemorrhages occurring during nephrostomic procedures is high (Jinga et al 2013;Kervancioglu et al 2014;Wang et al 2015); multiple embolizing agents have been reported, mainly coils/microcoils, gelatin sponge and particles.…”
Section: Introductionmentioning
confidence: 99%